Answer:
Option C. y= ( -x)^2 -4
Explanation:
If we have a function
and we want to transform it into a function g(x) that is equal to f(x) displaced c units down on the y-axis, then we must do:
![g(x) = f(x) -c](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rna906kzq549gnloqbhtmyyssu2j8wwar7.png)
In this case we want to move the function 4 units down, then:
![g(x) = f(x) -4\\\\g(x) = x ^ 2 -4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cbdsipurpfrug684l0lrfctjfzjt5e418u.png)
Finally, to reflect the function on the y-axis. must do
![y = g(-x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t4l9wahjd5j6akz5wtsvl7rxcplncwy81h.png)
Then we have the following function:
![g(-x) = (-x) ^ 2 -4\\\\y = (-x) ^ 2 -4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/b2g82mxuthc9rhhrbv7rgxpuvq3n5qx8b8.png)
The answer is option C